Transcriptome Characterization and Expression Analysis of Chemosensory Genes in Chilo sacchariphagus (Lepidoptera Crambidae), a Key Pest of Sugarcane - Liu, Jianbai; Liu, Huan; Yi, Jiequn; Mao, Yongkai; Li, Jihu; Sun, Donglei; An, Yuxing; Wu, Han (Frontiers in Physiology, 2021)
Insect chemoreception involves many families of genes, including odourant/pheromone binding proteins (OBP/PBPs), chemosensory proteins (CSPs), odourant receptors (ORs), ionotropic receptors (IRs) and sensory neuron membrane proteins (SNMPs), which play irreplaceable roles in mediating insect behaviours such as host location, foraging, mating, oviposition, and avoidance of danger. However, little is known about the molecular mechanism of olfactory reception in Chilo sacchariphagus, a major pest of sugarcane. A set of 76 candidate chemosensory genes, including 28 OBPs, 3 PBPs, 15 CSPs, 11 ORs, 13 IRs and 2 SNMPs, were identified in four transcriptomes from different tissues and genders of C. sacchariphagus. Phylogenetic analysis was conducted on gene families and paralogues from other model insect species. Quantitative real-time PCR (qRT-PCR) showed that most of these chemosensory genes exhibited antennae-biased expression, but some had high expression in bodies. Most of the identified chemosensory genes were likely involved in chemoreception. This study provides a molecular foundation for the function of chemosensory proteins, and an opportunity for understanding how C. sacchariphagus behaviours are mediated via chemical cues. This research might facilitate the discovery of novel strategies for pest management in agricultural ecosystems.